DEVELOPMENT OF INFORMATION TECHNOLOGY FOR MANAGING MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) - Asrul Sani (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The digitalization era has brought significant changes in the way of doing business, including for Micro, Small and Medium Enterprises (MSMEs). This research aims to examine the use of technology in increasing the productivity of MSMEs. Using qualitative and quantitative research methods, this study analyzes various technologies that can be adopted by MSMEs, such as e-commerce, social media, management information systems, mobile applications. Data was collected through surveys, interviews and case studies on a number of MSMEs that have successfully implemented technology in business operations. The research results show that technology adoption significantly increases operational efficiency, expands market reach, and improves the quality of MSME customer service. E- commerce and social media technologies have proven effective in increasing sales and brand awareness, while management information systems and mobile applications improve internal business processes and customer service. However, there are challenges, such as limited access to technology resources, lack of expertise in technology management, and data security issues. This research recommends building more inclusive digital infrastructure, technology training for MSME owners, and developing policies that support the MSME digital ecosystem. In conclusion, the use of technology is a critical strategy that MSMEs must implement to increase productivity and competitiveness in the global market.